Perbandingan Laju Fotosintesis pada Tanaman Tanjung (Mimusops elengi Linn.) dan Tanaman Merbau Darat (Intsia palembanica) pada Berbagai Media Tanam: Comparison of Photosynthesis Rates in Tanjung (Mimusops elengi Linn.) and Merbau Darat (Intsia palembanica) on Various Gowing Media - Hardiyanti, Rizky Ayu; Handayani, Rajjitha; Rif’atunidaudina, Ria; Rumondang, Jenny; Yandi, Wahyu Nazri; Muryunika, Rince; Puri, Suci Ratna (Jurnal Silva Tropika, 2025)
ABSTRACT Sunlight plays a crucial role in the process of photosynthesis because it provides the energy source that plants need. The intensity of light received by plants greatly affects their growth and the efficiency of photosynthesis. The rate of photosynthesis in plants is also greatly influenced by the intensity of sunlight, where if there is sufficient light intensity, adequate amounts of water and carbon dioxide, and appropriate temperatures, photosynthesis will usually reach its peak. The purpose of this research is to observe the rate of photosynthesis in Tanjung (Mimusops elengi Linn.) and Merbau darat (Intsia palembanica) plants with various treatments such as the addition of topsoil, subsoil, rice husk charcoal, cocopeat, sand, cow dung fertilizer, and NPK fertilizer using a plant photosynthesis meter. The research was conducted at the Educational Forest and Nursery Laboratory of the Forestry Department, Faculty of Agiculture, Jambi University. The results of this study indicate that Tanjung with the treatment of topsoil, rice husk charcoal, and 5 g of NPK is the best fertilizer application, as evidenced by the highest photosynthesis rate of 31.7 µmolCO2 m-2s-1. Meanwhile, for the merbau darat seedlings, the treatment with topsoil, sand, and 2 g of NPK fertilizer yielded the highest results for the photosynthesis rate.   Keywords: photosynthesis rate, NPK fertilizer, merbau darat, tanjung, subsoil   ABSTRACT Cahaya matahari sangat berperan dalam proses fotosintesis karena dapat memberikan sumber energi yang sangat dibutuhkan oleh tanaman. Intensitas cahaya yang diterima tanaman sangat mempengaruhi pertumbuhan dan efisiensi fotosintesis. Laju fotosintesis pada tanaman juga sangat di pengaruhi oleh intensitas cahaya matahari, dimana jika intensitas cahaya yang cukup, jumlah air dan karbon dioksida yang cukup serta suhu yang sesuai, fotosintesis biasanya akan mencapai puncaknya. Tujuan dari penelitian ini adalah untuk melihat seberapa tinggi laju fotosintesis pada tanaman Tanjung (Mimusops elengi Linn.) dan Merbau darat (Intsia palembanica) dengan berbagai perlakuan seperti penambahan media topsoil, subsoil, arang sekam, cocopeat, pasir, pupuk kotoran sapi dan pupuk NPK dengan alat plant photosyntesis meter. Penelitian dilakukan di Laboratorium Hutan Pendidikan dan Pembibitan Jurusan Kehutanan, Fakultas Pertanian Universitas Jambi. Hasil penelitian ini menunjukan bahwa tanaman Tanjung dengan pemberian perlakuan topsoil, arang sekam dan NPK 5 g merupakan pemberian pupuk terbaik dengan hasil laju fotosintesis tertinggi yaitu 31,7 µmolCO2m-2s-1. Sedangkan pada bibit merbau darat dengan pemberian perlakuan topsoil, pasir dan pupuk NPK 2 g mendapatlan hasil tertinggi untuk laju fotosintesisnya.   Kata kunci: laju fotosintesis, merbau darat, pupuk NPK, tanjung, subsoil